MARKETING MIX DAN TINGKAT MARGIN DALAM PENGAMBILAN KEPUTUSAN PEMBIAYAAN PADA NASABAH BANK SYARIAH - Sujono, Rusny Istiqomah; Wibowo, Febrian Wahyu (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
AbstractThe purpose of this study was to determine the effect of the marketing mix and margin levels on customer decisions. The design and methodology of this research is field research where the authors make observations to obtain the required data. Data is collected by giving questionnaires to customers who have several financial activities at the bank. The sample of this study was 100 respondents. The results showed that of the five Marketing mix variables, several variables significantly influenced customer interest, such as product, price, promotion, and margin level. However, place variables do not significantly influence customer decisions. Although not all marketing mix variables significantly influence customer interest, the marketing mix is still important for Islamic banks to attract customers